The impact of co-morbid mental and physical disorders on presenteeism - Amber Bielecky; Cynthia Chen; Selahadin Ibrahim; Dorcas E Beaton; Cameron A Mustard; Peter M Smith (Nordic Association of Occupational Safety and Health (NOROSH), 2015)
OBJECTIVES: This study sought to: (i) explore the impact of mood disorders (such as depression, bipolar disorder, mania, or dysthymia) and five age-related chronic physical conditions (arthritis, back pain, diabetes, heart disease, and hypertension) on presenteeism (as indicated by self-reported activity limitations at work), and (ii) examine how mood disorders interact with each physical condition to affect this work outcome. METHODS: Using Canadian Community Health Survey (CCHS) data, we modeled the relationships between self-reported restrictions at work and each health condition. We then calculated synergy indices (SI) for the interaction between mood disorders and each of the five physical conditions. RESULTS: All six health conditions were associated with presenteeism. The strongest association was observed for back pain [prevalence ratio (PR) 2.70, 95% confidence interval (95% CI) 2.57-2.83] and the weakest for hypertension (PR 1.18, 95% CI 1.11-1.25). The unadjusted SI indicated no interactions between mood disorders and any of the physical conditions, while the adjusted SI indicated statistically significant interactions between mood disorders and each of the five physical conditions. The statistically significant adjusted interactions were in a negative direction, such that having a mood disorder concurrent with a chronic physical condition was associated with a lower burden of presenteeism than expected. Post-hoc analyses revealed that this unexpected finding was attributable to adjustment for other co-morbid health conditions, particularly arthritis and back pain. CONCLUSIONS: Our results suggest that targeting chronic physical conditions or mood disorders may be productive in reducing presenteeism. The combined effect on presenteeism when the two types of conditions occur simultaneously is similar to the additive effect of these conditions when each occurs in isolation.